Waist‐to‐height ratio is as reliable as biochemical markers to discriminate pediatric insulin resistance - Rafael de Oliveira Alvim; Divanei Zaniqueli; Felipe Silva Neves; Virgilia Oliveira Pani; Caroline Resende Martins; Marcos Alves de Souza Peçanha; Míriam Carmo Rodrigues Barbosa; Eliane Rodrigues de Faria; José Geraldo Mill (Jornal de Pediatria (Versão em Português), 2019)
Objective: Given the importance of incorporating simple and low-cost tools into the pediatric clinical setting to provide screening for insulin resistance, the present study sought to investigate whether waist-to-height ratio is comparable to biochemical markers for the discrimination of insulin resistance in children and adolescents. Methods: This cross-sectional study involved students from nine public schools. In total, 296 children and adolescents of both sexes, aged 8–14 years, composed the sample. Waist-to-height ratio, triglycerides/glucose index, and triglycerides-to-HDL-C ratio were determined according to standard protocols. Insulin resistance was defined as homeostatic model assessment for insulin resistance with cut-off point ≥ 3.16. Results: Age, body mass index, frequency of overweight, waist circumference, waist-to-height ratio, insulin, glucose, homeostatic model assessment for insulin resistance, triglycerides, triglycerides/glucose index, and triglycerides-to-HDL-C were higher among insulin resistant boys and girls. Moderate correlation of all indicators (waist-to-height ratio, triglycerides/glucose index, and triglycerides-to-HDL-C ratio) with homeostatic model assessment for insulin resistance was observed for both sexes. The areas under the receiver operational characteristic curves ware similar between waist-to-height ratio and biochemical markers. Conclusion: The indicators provided similar discriminatory power for insulin resistance. However, taking into account the cost-benefit ratio, we suggest that waist-to-height ratio may be a useful tool to provide screening for insulin resistance in pediatric populations. Resumo: Objetivo: Considerando a importância de incorporar ferramentas simples e de baixo custo no cenário clínico-pediátrico para a triagem de resistência à insulina, o presente estudo buscou investigar se a razão cintura/estatura é comparável a marcadores bioquímicos na discriminação de resistência à insulina em crianças e adolescentes. Métodos: Este estudo transversal envolveu estudantes de nove escolas públicas. No total, 296 crianças e adolescentes, de ambos os sexos, com idades entre 8 e 14 anos, compuseram a amostra. A razão cintura/estatura, o índice triglicerídeos/glicose e a razão triglicerídeos/HDL-C foram determinados de acordo com protocolos padrão. A resistência à insulina foi definida por meio do modelo de avaliação homeostática para resistência insulínica, com ponto de corte ≥ 3.16. Resultados: Idade, índice de massa corporal, frequência de excesso de peso, circunferência da cintura, razão cintura/estatura, insulina, glicemia, modelo de avaliação homeostática para resistência insulínica, triglicerídeos, índice triglicerídeos/glicose e razão triglicerídeos/HDL-C foram maiores entre meninos e meninas com resistência à insulina. Também foram observadas, em ambos os sexos, correlações moderadas de todos os indicadores (razão cintura/estatura, índice triglicerídeos/glicose e razão triglicerídeos/HDL-C) com o modelo de avaliação homeostática para resistência à insulina. As áreas sob as curvas ROC foram semelhantes entre a razão cintura/estatura e os marcadores bioquímicos. Conclusão: Os indicadores forneceram poder discriminatório similar para a resistência à insulina. No entanto, levando em conta o custo-benefício, sugerimos que a razão cintura/estatura pode ser uma ferramenta útil para a triagem de resistência à insulina em populações pediátricas. Keywords: Children, Adolescents, Insulin resistance, Triglycerides/glucose index, Triglycerides‐to‐HDL‐C ratio, Waist‐height ratio, Palavras‐chave: Crianças, Adolescentes, Resistência à insulina, Índice de triglicerídeos/glicose, Razão triglicérides‐HDL‐C, Razão cintura‐altura